Knowledge on Digital Health and its Associated Factors among Undergraduate Public Health Students of Nepal - Dipesh Shrestha; Jamuna Gautam; Pramana Adhikari; Mahesh Bhatta (Nepal Journal of Public Health, 2026)
Background: Digital health spans telehealth, mHealth, wearables, and electronic health records. Nepal has committed through the Digital Nepal Framework (2019) and e-Health Strategy, yet whether Bachelor of Public Health (BPH) programs equip students with the relevant skills remains an open question. The objective of this study was to assess the level of knowledge on digital health and its associated factors among undergraduate public health students of Nepal. Methods: A web-based cross-sectional survey among 275 BPH students drawn from three universities and two academies in Nepal via convenience sampling. A self-administered Google Forms questionnaire containing socio-demographics, prior digital health exposure, and responses to 20 multiple-choice items across five domains (general digital health, telehealth, mHealth, wearable devices, and EHR). We tested associations with Pearson's Chi-square, the Fisher–Freeman–Halton Exact test (significance set at p < 0.05) and binary logistic regression. Results: Students scored a mean of 79.69% (SD = 17.43). Among them 55.6% fell in the high-knowledge category, 35.6% moderate, and 8.7% low. Despite these scores, 91.3% reported low prior exposure. Age group (p = 0.0042), household income (p = 0.0002), and academic year (p = 0.0236) show significance to knowledge level. On further applying binary logistic regression, only age category shows significance to knowledge level. Conclusions: BPH students scored well overall, but their knowledge is gained informally rather than coursework. The existing curriculum is not empowering the students for digitally oriented workforce needs. A dedicated digital health module and a standardized competency framework should be priorities in the current round of curriculum reform.